An integrated real-time traffic signal system for transit signal priority, incident detection and congestion management. (November 2015) - Ahmed, F.; Hawas, Y.E.
Highlights: A signal control model for incident detection and transit system priority is presented. Micro-simulation methodology is adopted to test the integrated model. The developed model is interfaced with CORSIM for assessment. Various signal control types, network geometry, and demand levels are considered. Model's efficiency and productivity are compared against CORSIM controllers' values. Abstract: This paper presents a traffic control system that can work standalone to handle various boundary conditions of the recurrent, non-recurrent congestion, transit signal priority and downstream blockage conditions to improve the overall traffic network vehicular productivity and efficiency. The control system uses field detectors' data to determine the boundary conditions of all incoming and exit links. The developed system is interfaced with CORSIM micro-simulation for rigorous evaluations with different types of signal phase settings. The comparative performance of this control logic is quite satisfactory for some of the most frequently used phase settings in the network with a high number of junctions under highly congested conditions.